Managing Biological Risks in Biomedical laboratories of Public Hospitals in Athens, Greece, based on the Biosafety requirements - Dionysios Vourtsis; Efstathia Papageorgiou; Anastasios Kriebardis; George Albert Karikas; Gijsbert van Willigen; Kostas Kotrokois; Georgios Dounias; Petros Karkalousos (European Scientific Journal, ESJ, 2025)
Objectives: The aim of the present study was to review the laboratory workers’ perception on the biological risks in biomedical laboratories of public hospitals in Athens, Greece. It was also to evaluate how they are managing the biological materials and to propose mitigation measures according to the existing risks, based on the local legislation and the international Biosafety guidelines. Materials and Methods: The study was designed as a cross-sectional study with a detailed health and safety (H&S) questionnaire focused on biosafety and biorisk management. A total of 36 biosafety level-2 biomedical laboratories in 20 public hospitals were assessed for their biosafety containment specifics and compliance with biosafety practices. Laboratory staff (medical laboratory doctors, medical laboratory technologists, laboratory assistants, biologists and biochemists, n = 415) completed the questionnaire. Results and Discussion: The results showed, that a significant percentage of laboratories lacked proper management of the biological agents and biological materials in general, as could be seen in the following reduced percentage data: restricted access (48.9%), controlled and independent ventilation (36.6%), use of BSCs (31.8%), biorisk management system in place (31.6%), risk assessments (28.4%), biosafety manuals (21.4%), SOPs (35.9%), assigned biosafety officers (10.8%), occupational medical doctor (34.9%), emergencies plan (34.2%), accidents reporting (25.5%), and biosafety training programs (28.2%). Conclusion: There are marked deficiencies in containment and administrative controls, as well as in the implementation of the Greek and EU biosafety legislation. This emphasize the urgency of addressing critical gaps in biosafety and in emergency preparedness in Greek biomedical laboratories. Therefore, a Biorisk Management System, risk assessments, SOPs, assignment of Biosafety Officers, staff trainings and emergency response plans should be developed, applied and enforced, in compliance with the local and European legislation and guidelines.